A Lattice‐Oxygen‐Involved Reaction Pathway to Boost Urea Oxidation. (11th October 2019) - Zhang, Longsheng; Wang, Liping; Lin, Haiping; Liu, Yunxia; Ye, Jinyu; Wen, Yunzhou; Chen, Ao; Wang, Lie; Ni, Fenglou; Zhou, Zhiyou; Sun, Shigang; Li, Youyong; et al.
Abstract: The electrocatalytic urea oxidation reaction (UOR) provides more economic electrons than water oxidation for various renewable energy‐related systems owing to its lower thermodynamic barriers. However, it is limited by sluggish reaction kinetics, especially by CO2 desorption steps, masking its energetic advantage compared with water oxidation. Now, a lattice‐oxygen‐involved UOR mechanism on Ni 4+ active sites is reported that has significantly faster reaction kinetics than the conventional UOR mechanisms. Combined DFT, 18 O isotope‐labeling mass spectrometry, and in situ IR spectroscopy show that lattice oxygen is directly involved in transforming *CO to CO2 and accelerating the UOR rate. The resultant Ni 4+ catalyst on a glassy carbon electrode exhibits a high current density (264 mA cm −2 at 1.6 V versus RHE), outperforming the state‐of‐the‐art catalysts, and the turnover frequency of Ni 4+ active sites towards UOR is 5 times higher than that of Ni 3+ active sites. Abstract : 4+ gewinnt : Die Harnstoffoxidation (UOR) an aktiven Ni 4+ ‐Zentren unter Beteiligung von Gittersauerstoff verläuft deutlich schneller als die herkömmliche UOR an aktiven Ni 3+ ‐Zentren. Der entsprechende Ni 4+ ‐Katalysator an einer Glaskohlenstoffelektrode zeigt eine hohe Stromdichte von 264 mA cm −2 bei 1.6 V gegen die reversible Wasserstoffelektrode (RHE) und übertrifft damit modernste Ni 3+ ‐Katalysatoren.